Sistem Administrasi Perpajakan Modern Dan Kesadaran Wajib Pajak Terhadap Kepatuhan Wajib Pajak Orang Pribadi Pengusaha Muda - Fitri, Nur Annisa Idul; Allo Layuk, Paulus K; Seralurin, Yohanes C (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2022)
This study aims to determine the effect of implementing a modern tax administration system and awareness of taxpayers on individual taxpayer compliance of young entrepreneurs in Jayapura City. The population of this study is individual taxpayers of young entrepreneurs in Jayapura City. The sampling technique used in this study was purposive sampling. The number of samples used is 69 samples. Source of data in this study is primary data, with data collection method using a questionnaire. The measurement scale used in the questionnaire is the Likert scale. Data analysis using multiple linear regression statistical tools with the help of statistical software SPSS 25. The research results obtained are that the application of a modern tax administration system and taxpayer awareness has a significant effect on individual taxpayer compliance of young entrepreneurs in Jayapura City.